Serum bone markers in pregnant women at Parirenyatwa Group of Hospitals and Chitungwiza Central Hospital (Bangladesh Journal of Medical Science, 2015)
Background: Pregnancy induces a number of physiological changes in the body including changes in bone profile. As the gestational period progresses and the foetus grows, its demand for mineral micronutrients increases inducing changes in the maternal body. Serum bone profile varies according to trimester as gestational period progresses. The study on which this article is based sought to determine changes in bone profile with trimester in pregnant women attending antenatal clinic at Parirenyatwa Group of Hospitals (PGH) and Chitungwiza Central Hospital, Zimbabwe. Method: An analytical cross sectional study was conducted on pregnant women attending antenatal clinics at Parirenyatwa Group of Hospitals and Chitungwiza Central Hospital. A questionnaire was administered and blood samples were collected for analysis of albumin, corrected calcium, phosphate and alkaline phosphatase. Results: A total of 171 pregnant women were recruited into the study. The albumin level showed a significant fall from trimester 1 to 2 (P0.05). Conclusion: This study confirms the previously reported constant serum inorganic phosphate level throughout the gestational period and an increase in alkaline phosphatase with gestational age. Corrected calcium level had a statistically significant increase from the second to the third trimester (P